Leprosy and its dental management guidelines. (5th February 2013) - Dave, Bella; Bedi, Raman
<x xml:space="preserve">Abstract</x> Objectives Leprosy is a chronic, non‐fatal disease caused by Mycobacterium leprae. It can cause cutaneous lesions, peripheral nerve lesions and orofacial manifestations, including destruction of the alveolar premaxillary process associated with loss of the maxillary incisors. The aims of this study were to assess orofacial manifestations of disease in patients attending the Bombay Leprosy Project clinics and develop clinical guidelines for dentists. Materials and methods A cross‐sectional questionnaire based study was administered to 43 diagnosed leprosy patients. This included questions on perceived oral health status and oral hygiene habits. An extra‐oral and intra‐oral examination was also performed. Results Eighty‐four per cent of patients were male with a mean age of 35.9 years. Forty‐nine per cent had extra‐oral cutaneous lesions. Twenty‐eight per cent had intra‐oral lesions including hyperpigmented patches. Twenty‐one per cent had cranial nerve involvement and the trigeminal nerve was most commonly affected. Conclusions From this data a clinical dental pathway protocol for managing patients with leprosy was developed. It highlights dental issues when managing leprosy patients. Nerve involvement may mean patients are unable to give an accurate account of their symptoms. Special tests should include cranial nerve examination and swabs of intra‐oral ulcers. Low rates of infectivity means that normal infection control measures can be taken when treating these patients.